2013
DOI: 10.1073/pnas.1305560110
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the processive rubber oxygenase RoxA from Xanthomonas sp

Abstract: Rubber oxygenase A (RoxA) is one of only two known enzymes able to catalyze the oxidative cleavage of latex for biodegradation. RoxA acts as a processive dioxygenase to yield the predominant product 12-oxo-4,8-dimethyl-trideca-4,8-diene-1-al (ODTD), a tri-isoprene unit. Here we present a structural analysis of RoxA from Xanthomonas sp. strain 35Y at a resolution of 1.8 Å. The enzyme is a 75-kDa diheme c -type cytochrome with an unusually low degree of secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 45 publications
(60 reference statements)
1
54
0
1
Order By: Relevance
“…Carbon monoxide is able to bind to RoxA Xsp in the form as isolated, as revealed by the CO-dependent appearance of an absorption peak at 415 nm in the difference spectrum (21). This binding can be explained by the CO affinity of the reduced, oxygen-bearing heme center (10). Carbon monoxide strongly inhibits the polyisoprene cleavage reaction of RoxA Xsp (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon monoxide is able to bind to RoxA Xsp in the form as isolated, as revealed by the CO-dependent appearance of an absorption peak at 415 nm in the difference spectrum (21). This binding can be explained by the CO affinity of the reduced, oxygen-bearing heme center (10). Carbon monoxide strongly inhibits the polyisoprene cleavage reaction of RoxA Xsp (21).…”
Section: Resultsmentioning
confidence: 99%
“…Production and excretion of RoxB Xsp , containing two costly cofactors, would not seem advantageous for the bacteria if they are not able to use the reaction products for metabolism. One reason for the presence of a roxB gene might be the fact that RoxA Xsp is an exo-type cleavage enzyme that needs free polyisoprene ends to cleave the polymer in a processive manner to give the only observed end product, ODTD (10). The presence of RoxB Xsp , which cleaves rubber in an endo-type fashion to a mixture of oligo-isoprenoids, would enlarge the number of poly/oligo-isoprenoid chains with free, accessible ends.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous structural and biophysical analysis had revealed that the heme group of the RoxA active site has a dioxygen molecule bound to the heme iron atom of the active heme site (11,13). Because of the strong electronegativity of oxygen, one electron of the Fe 2ϩ ion is relocated to the dioxygen molecule, resulting in an Fe 3ϩ -O 2 Ϫ state.…”
Section: Uv-vis Spectroscopy Of Lcpmentioning
confidence: 99%
“…strain 35Y (9). Biochemical and biophysical investigation revealed that RoxA is an extracellular dioxygenase with two covalently attached heme groups (10,11) and is structurally but not functionally related to cytochrome c peroxidases (12,13). RoxA cleaves poly(cis-1,4-isoprene) to 12-oxo-4,8-dimethyltrideca-4,8-diene-1-al (ODTD; C 15 -tri-isoprenoid) as a main end product.…”
mentioning
confidence: 99%